Despite antiretroviral therapy (ART) rollout, most cases of tuberculosis among people with HIV in Adama, Ethiopia, occur before ART initiation - Patrik Bristedt; Meseker Fentie; Per Björkman; Anton Reepalu (Taylor & Francis Group, 2024)
Introduction Although antiretroviral therapy (ART) leads to reduced tuberculosis (TB) incidence in people with HIV (PWH), ART recipients remain at higher risk of TB compared to HIV-seronegative people. With accelerated ART rollout in sub-Saharan Africa, increasing proportions of TB cases among PWH in people receiving long-term ART have been reported. Objective To determine TB notifications among PWH by ART status in a mainly urban uptake area in Ethiopia during an 8-year period in connection to the introduction of the 'test-and-treat' strategy for HIV. Methods PWH were identified from registers at health facilities providing ART in Adama and surrounding areas, Ethiopia 2015-2022. Annual TB notifications were compared over time. PWH within TB were categorized by ART status at the time of TB diagnosis (pre-ART TB: TB diagnosed before or ≤6 months after starting ART; ART-associated TB: TB diagnosed >6 months after starting ART). Results Among a total of 8,926 PWH, 993 had been diagnosed with TB (11.1%); mean age 40.0 years [SD 11.8], 53.5% were men). Throughout the study period, most TB cases had been notified before ART initiation (617/993; 62.1%). ART-associated TB cases constituted a mean of 37.4% (range 23.8%-44.2%) of all TB cases among PWH annually. Median time from ART initiation to TB diagnosis among ART-associated TB was 6.0 years. Conclusion TB notifications among PWH in this area did not decrease 2015-2022, implying persistently high risk of TB among PWH in this setting. Most TB cases occurred in ART-naïve persons, illustrating late HIV diagnosis in this population.